Persepsi Komunikasi Risiko Covid 19 Masyarakat Warung Kopi di Kota Banda Aceh - Hamdani M. Syam; Marzuki Marzuki; Deni Yanuar (Communicatus: Jurnal Ilmu komunikasi, 2021)
This study aims to look at risk communication behavior and its relationship with the perception of Covid-19 risk in the coffee shop community in Banda Aceh City. This study uses a quantitative approach with a sample of 829 respondents, namely coffee shop visitors. The study results indicate a relationship between Covid-19 risk communication and the coffee shop community's perception of risk in Banda Aceh City. The value of the closeness of the relationship is 0.723. Meaning has an extreme level of intimacy. This study also found that risk communication and perception positively affect the association. Thus, it can be said that if risk communication increases, the community's perception of Covid-19 risk will increase as well. However, if Risk Communication decreases, the perception of Covid-19 risk that the coffee shop community in Banda Aceh City has will also decrease.